(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
Two methods for the synthesis of 2,4-dihydroxy-3-(3’-chloro-2-buthenyI) quinolines are developed. By intermolecular cyclisation of o-ethoxycarbonylanilide of 4-chloro-3-pentencarbonic acid in the presence of sodium alcoholate or sodium suspension in xylene and by the thermal intermolecular cyclisation of monoanilide of 3- chloro-2-buthenylmalonic acid ethyl ester.